HUBUNGAN ANTARA IKLIM ORGANISASI DENGAN KEPUASAN KERJA PADA KARYAWAN PT CIPTA NIAGA SEMESTA CABANG BEKASI - Dea Fauzia Ridlwan; Rr Ponco Dewi K (Fakultas Ekonomi Universitas Negeri Jakarta, 2014)
ABSTRACTThe purpose of this research is to detect correlation between climate organization with job satisfaction on employees PT Cipta Niaga Semestat. The research is done during for two months since April until Mai 2014. The method of research is survey method with correlation approach. The population research was all of employees with total 60 employees, and 51 employees for sampling and used simple random sampling. Instrument that used to get variable data X (Climate Organization) measured by questionnaire using Likert Scale. For Variable Y (Job Satisfaction) was also measured by questionnaire using Likert Scale. The analysis test by finding regression equation, that is Å¶ = 35,58 + 0,513X, while analysis rules test that is test normalitas while analysis rules test that is test normalitas regression estimation error Y on X with test liliefors got Lhitung0,090 < Ltabel 0,124, matters this means sample comes from population normal distribution. Significancy test and regression linearity by using analysis table varians (anava) got regression similarity Fhitung 25,12 > Ftabel 4,14 that declare regression very mean with regression linearity test that produce Fhitung 0,85 < Ftabel 2,0 that show that regression model that used linear. Correlation coefficient hypothesis test is done with formula product moment produce rxy as big as 0,582. Significancy test with thitung as big as 5,01 dan ttabel 1,68. Because tcount < ttabel, from watchfulness result so researcher can conclude that found connection significant between climate organization with job satisfaction on employee PT Cipta Niaga Semesta. Determination coefficient test produces KD as big as 33,89 %. So can be taken conclusion found which are positive connection and significant between climate organization and job satisfaction.Keywords : Job Satisfaction, Climate Organization